Potensi Pantai Anyer Sebagai Objek Wisata Utama di Provinsi Banten - Muhammad Zuhal Mujahid (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2023)
This research is conducted based on the tourism situation in Anyer Beach, Serang Regency, Banten Province. The issue of environmental sustainability has motivated the author to explore the potential optimization of Anyer Beach as the main tourist attraction in Banten. It’s beautiful natural resources and modernization in the present era have made Anyer Beach one of the potential tourist destinations and capable of being the main tourist attraction in Banten. Administratively, Anyer Beach is in Anyar District, at the western tip of Serang Regency, Banten Province. The main tourist attractions in this area are the long and wide coastal areas facing the Sunda Strait, which consist of Anyer Beach, Tanjung Tum Beach, Bojong Beach, and Sambolo Beach. These four beaches are interconnected from north to south in Anyar District, with a total coastline length of 25 km. Anyer Beach, Tanjung Tum Beach, and Sambolo Beach are generally covered with coarse sand, fine sand, and gravel. In addition to sand and gravel, Bojong Beach also features a Lighthouse Tower built during the Dutch colonial era. The Anyer Beach area has been equipped with various accommodation facilities such as hotels, villas, resorts, guesthouses, healthcare facilities, restaurants, clean water supplies, electricity, security, and more. All these facilities have a positive impact on the progress of Anyer Beach's potential as the main tourist attraction in Banten. With adequate facilities, tourists will be interested in visiting.